(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Employing annual time series data on the number of people who practice open defecation in Zimbabwe from 2000 – 2017, the study predicts the annual number of people who will still be practicing open defecation over the period 2018 – 2022. The study applies the Box-Jenkins ARIMA approach. The diagnostic ADF tests show that the series under consideration is an I (1) variable. Based on the AIC, the study presents the ARIMA (3, 1, 0) model as the optimal model. The diagnostic tests further reveal that the presented parsimonious model is indeed stable and its residuals are not only stationary in levels but also normally distributed. The results of the study indicate that the number of people practicing open defecation in Zimbabwe is likely to decline over the period 2018 – 2022, from 25% to approximately 23.7% of the total population. In order to sustain this desirable downwards trend, the study suggested a three-fold policy recommendation to be put into consideration, especially by the government of Zimbabwe and its partners in water, sanitation and hygiene (WASH) related programmers.